If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 0 = -4(x + 5) Reorder the terms: 0 + y = -4(x + 5) Remove the zero: y = -4(x + 5) Reorder the terms: y = -4(5 + x) y = (5 * -4 + x * -4) y = (-20 + -4x) Solving y = -20 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -20 + -4x
| 17x+3=4(4x+5) | | z(-5-5*-5)=45 | | H(8)=456t | | -3x-15=-(3x+15) | | 3*0.8= | | 7(6y-8)=14y | | 5+16f=-9+16 | | a+4-8=-9 | | 4+9x=-59 | | 11/20+-34= | | 12-5d=7d | | 4k+5+6k+10=115 | | 6x-2-3x=x+8+x | | z(x-5x)=45 | | 11y=10(y+12) | | 500-35= | | 17x+90+4x=9+x | | 2x-4x+3=17 | | 236*3=n | | 2x(4+x)=78 | | y+1=-9(x+3) | | 6m^2+14m+4=0 | | z(x-5x)=210 | | 50=14-4x | | 4x+23=9x-31 | | z(x-5*-5)=210 | | 3y-9whenY=19 | | 7x-5+x-3= | | .20x+.35(50)=27.5 | | y=30+.20x | | 8x(-6)=8 | | y=-x^2+39x-270 |